COVID-19: INSIDE INDONESIA’S ISLAMIC STATE SOCIAL MEDIA NETWORK - Prakoso Permono (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2020)
ISIS affiliates in Indonesia have been involved actively in social media particularly during the Covid-19 pandemic. This article is trying to explore and analyze Islamic State affiliates daily narrative in their social media network based on digital ethnography conducted between March to July 2020 following the Covid-19 outbreak. The ethnography focuses on four ISIS affiliate’s Telegram channel and group. We found that ISIS affiliates in Indonesia as a rational actor have been capitalizing opportunities brought by Covid-19 and vulnerabilities in Indonesia’s society to strengthen radicalization and grassroots support from broader Muslim communities. This research also finds more advanced and personalized anti-government and anti-Chinese rhetoric being emphasized by Islamic State affiliates in Indonesia during the pandemic and concludes that behind Indonesian ISIS narratives during the Covid-19 pandemic emerges a clandestine imminent threat to the society.